Learning to Create a Blend through Podcasts A Case Study - D’Souza, Russell (JOURNAL OF INDIAN EDUCATION, 2017)
Learning through technology is a gateway to acquisition and processing of information. A plethora of digital technologies, including podcasts can make learning interesting, enriching and efficient, thereby adding a blend and taste to learning. As teachers are crucial partners in the learning process, they need to be equipped with a variety of digital skills to create digital learning material such as podcasts. The paper focuses on enabling student-teachers to understand the dynamics of podcasts, create them, measure their attitude towards the developed podcasts and also their reaction to use of podcasts in learning.